Efficiency of five-year learning cycle strategy on achievement in discus throwing event (College of Basic Education Research Journal, 2025)
Study aimed to identify  efficiency of  five-year learning cycle strategy on achievement in discus throwing , as well as knowing  differences between  two research groups (experimental and control) between post-tests in cognitive , skill  and achievement of  discus throwing.          Researcher assumed that there was a significant difference in  results of  two research groups (experimental and control) between  pre- and post-tests in   discus throwing , in addition to a significant difference in  results of  two research groups (experimental and control) between post tests of achievement in discus throwingResearch community was determined in a deliberate manner, represented by  students of  second stage  in  Department of Physical Education and Sports Sciences - College of Basic Education / University of Mosul for the academic year (2023-2024). Total number of students in this stage (81) male and female students distributed over three classes . First class contained (26) students,  second (25) , and  third (30) male and female students, divided into (20) male and (10) female students. Researcher used  statistical package (25 - SPSS) to obtain results . Researchers concluded.Efficiency of  five-year learning cycle strategy and current method used in developing skill attainment and achievement for  two research groups (experimental and control). In  discus throwing .Experimental group that applied  five-year learning cycle strategy outperformed  control group in cognitive achievement of  discus throwing.Reaching these results,  researcher made several recommendations, the most important of which was:Necessity of adopting and applying  five-year learning cycle strategy in the process of teaching  discus throwing , in order to demonstrate its effectiveness in gaining cognitive and skill achievement and achieving this event, as well as  adopting and applying  five-year learning cycle strategy